Driver sleepiness and risk of serious injury to car occupants: population based case control study. Issue 7346 (11th May 2002) - Connor, Jennie; Norton, Robyn; Ameratunga, Shanthi; Robinson, Elizabeth; Civil, Ian; Dunn, Roger; Bailey, John; Jackson, Rod
Abstract: Objectives: To estimate the contribution of driver sleepiness to the causes of car crash injuries. Design: Population based case control study. Setting: Auckland region of New Zealand, April 1998 to July 1999. Participants: 571 car drivers involved in crashes where at least one occupant was admitted to hospital or killed ("injury crash"); 588 car drivers recruited while driving on public roads (controls), representative of all time spent driving in the study region during the study period. Main outcome measures: Relative risk for injury crash associated with driver characteristics related to sleep, and the population attributable risk for driver sleepiness. Results: There was a strong association between measures of acute sleepiness and the risk of an injury crash. After adjustment for major confounders significantly increased risk was associated with drivers who identified themselves as sleepy (Stanford sleepiness score 4-7 v 1-3; odds ratio 8.2, 95% confidence interval 3.4 to 19.7); with drivers who reported five hours or less of sleep in the previous 24 hours compared with more than five hours (2.7, 1.4 to 5.4); and with driving between 2 am and 5 am compared with other times of day (5.6, 1.4 to 22.7). No increase in risk was associated with measures of chronic sleepiness. The population attributable risk for driving with one or more of the acute sleepiness risk factors was 19% (15% to 25%). Conclusions: Acute sleepiness in car drivers significantly increases the risk of a crash in which a car occupant is injured or killed. Reductions in road traffic injuries may be achieved if fewer people drive when they are sleepy or have been deprived of sleep or drive between 2 am and 5 am.